Implementation of the Sentra-ku Application at the Regional Financial and Asset Management Agency in Pasangkayu Regency - Alfianti Tapala, Alma; Haedar Akib; Herman H; Sudiarti Dewi Kurra; Nur Fadilah Guntur (Universitas Negeri Makassar, 2025)
This study investigates the implementation of the Sentra-ku Application at the Regional Financial and Asset Management Agency (BPKAD) of Pasangkayu Regency, addressing operational challenges and identifying factors that support and inhibit its effectiveness. A key issue examined is the internal recording of financial transactions, including tax budgets and treasury operations, which were previously not fully integrated into existing applications. This research employs a qualitative approach with a case study design, utilizing data collection techniques such as observation, in-depth interviews, and documentation. The data analysis process involves data condensation, data presentation, and conclusion drawing to ensure comprehensive insights. The findings highlight several critical aspects of the implementation process. In terms of communication, the process was effective, evidenced by structured and multi-method communication strategies with implementers, including the use of questionnaires to evaluate employee understanding. Resource-wise, while most BPKAD employees demonstrated proficiency in operating the Sentra-ku Application, more advanced and complex features required additional IT team support. Regarding disposition, employees recognized the importance of the application and exhibited strong support for its implementation. This was further reinforced by the proactive involvement of the BPKAD head, who actively guided the development and implementation stages, ensuring alignment with organizational goals. The bureaucratic structure within BPKAD was identified as being flexible and adaptive to changes, significantly supporting the smooth implementation of the Sentra-ku Application. Key supporting factors included effective communication, clear and consistent transmission of policy information, adequate resources in terms of both quantity and quality, and positive employee attitudes toward change. Furthermore, an efficient and responsive bureaucratic structure played a pivotal role in facilitating implementation success. However, inhibiting factors were also identified, such as insufficient policy support, lack of critical information, inadequate support systems, and improper delegation of responsibilities and authority. This study underscores the importance of clear communication, sufficient resources, strong leadership, and adaptable organizational structures in ensuring the effective implementation of digital innovations like the Sentra-ku Application. These findings provide valuable insights for policymakers and organizations aiming to improve financial management systems in public institutions.